Computational Analysis of an Effect of Aerodynamic Pressure on the Side View Mirror Geometry - P., Murukesavan; N. M. M., Ammar; M. S., Idris (2013)
This paper describes the evaluation of aerodynamic flow effects on side mirrors geometry for a passenger car using ANSYS Fluent CFD simulation software. Result from analysis of pressure coefficient on the side view mirror designs is evaluated to analyze the unsteady forces that cause fluctuations to mirror surface and image blurring. The fluctuation also causes drag forces that increase the overall drag coefficient, with an assumption resulting in higher fuel consumption and emission. Three Features of side view mirror design were investigated with two input velocity parameters of 17 m/s and 33 m/s. Results indicate that the half-sphere design shows the most effective design with less pressure coefficient fluctuation and drag coefficient.